Under the knife: Unfavorable perceptions of women who seek plastic surgery. - Sarah Bonell (Public Library of Science (PLoS), 2021)
Plastic surgery is growing in popularity. Despite this, there has been little exploration to date regarding the psychosocial consequences of seeking plastic surgery. Our study investigated how women seeking plastic surgery are perceived by others. We presented a random sample of 985 adults (men = 54%, Mage = 35.84 years, SDage = 10.59) recruited via Amazon's Mechanical Turk with a series of experimental stimuli consisting of a photographed woman (attractive versus unattractive) and a vignette describing an activity she plans to engage in (plastic surgery versus control activity). Participants rated stimuli on perceived warmth, competence, morality, and humanness. We ran linear mixed-effect models to assess all study hypotheses. There was a negative plastic surgery effect; that is, women seeking plastic surgery were perceived less favorably than those planning to complete control activities across all outcome variables (warmth, competence, morality, and humanness). These relationships were moderated by physical attractiveness; while attractive women planning to undergo plastic surgery were perceived less favorably than attractive women planning to engage in control activities, perceptions of unattractive individuals remained unchanged by plastic surgery status. We theorized that empathy toward unattractive women seeking plastic surgery mitigated the negative plastic surgery effect for these women. In sum, our results suggest that perceptions of attractive women are worsened when these women decide to seek cosmetic surgery. Perceptions of warmth and competence have implications for an individual's self-esteem and interpersonal relationships, while perceptions of morality and humanness can impact an individual's ability to fulfil their psychological needs. As such, we concluded that attractive women seeking plastic surgery are potentially subject to experience negative psychosocial outcomes. Future research ought to examine whether perceptions and outcomes differ for women seeking reconstructive plastic surgery (versus cosmetic plastic surgery) and whether they differ across different types of surgeries (i.e. face versus body).